Prevalence and subjective knowledge of tongue lesions in an Indian population - Preeti Tomar Bhattacharya; Rupam Sinha; Sumona Pal (Journal of Oral Biology and Craniofacial Research)
Aim: The current study was designed to determine prevalence of various tongue lesions and their association with age, gender, systemic illness, deleterious habits, and distribution over the surfaces of tongue. It also explored the awareness and knowledge of subjects in relation to presence of tongue lesions, etiological factor, symptoms, and treatment received if any. Methods: The present study was conducted on 1360 randomly selected dental outpatients from 1/10/2013 to 30/09/2014. Examination of tongue included surface changes, size, movements, and the presence of mucosal lesions. The subjects were asked about the knowledge, symptoms, and treatment obtained in case of awareness regarding the lesion. Results: The prevalence of tongue lesions was found to be 13.75%. The most prevalent lesion was found to be coated tongue. The majority of the lesions were located on dorsum of tongue and not related with age, gender, habit, and systemic condition. A considerable number of subjects were aware of the changes on their tongue but negligible number sought any treatment. Conclusions: The presence of tongue lesions in the study population was found be significant. Hence, general dental practitioners and health care providers should be educated about the diagnosis, etiology, investigations, and proper management of such tongue lesions.